PENDIDIKAN TOLERANSI DALAM MASYARAKAT MULTIKULTURALISME (Kajian Masyarakat Multikultur di Kelurahan Fajar Esuk Kabupaten Pringsewu): (Kajian masyarakat multikultur di Kelurahan Fajar Esuk) - Eri Purwanti; Muhtarom Muhtarom; Muhammad Idris (STIT PRINGSEWU, 2023)
This research aims to describe the basis, form and value of local wisdom and the pattern of the formation of a multicultural society in Fajar Esuk village. This study uses a qualitative approach with ethnographic analysis methods as a basis for interpreting elements of tradition and culture in a multicultural society. The results of this study indicate that cosmic multiculturalism is the basis for the formation of a society with high tolerance among community members. Furthermore, there are four influences that form the basis of this, namely the influence of cultural studies, globalization, unblocking gender, mindset. Various local wisdoms become media and patterns of tolerance in a multicultural society, including the commemoration of religious holidays, Hajatan. Wiwitan and joint economic development activities.